Seasonal influence on polymorphic flowering behaviour, fruitset and seed recovery in brinjal (Solanum melongena L.) cultivars - Raja, K (Bangladesh Journal of Botany, 2021)
Flowering behavior in brinjal (Solanum melongena L.) shows that it produces four type of flowers viz., long, medium, short and pseudoshort styled flowers. Among these flowers, the long and medium styled flowers have the biggest ovary and set fruits in both the cultivars viz., PLR 1 and PLR (Br.) 2. Whereas, short and pseudoshort styled flowers did not set fruits. In addition, the highest fruitset (84.7%) was recorded in long styled flowers than the medium styled flowers (77.7%). However, no significant difference in seed recovery was observed in the fruits from long and medium styled flowers. The seasonal influence on flowering and fruitset was also noticed; in which, Kharif season with less difference in day-night temperatures, high rainfall and relative humidity and less wind velocity favoured occurrence of more number of long and medium styled flowers with high fruitset in both the cultivars.